The Position of Teachers in the Development of Early Childhood Character Education - Munafiah, Nida'ul; Novianti, Cucu; Ferianto, Ferianto (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
The teacher's position once looked down upon, is now considered a professional and even stipulated in Law no. 14 of 2005 Chapter II Article 2. Therefore, the position of the teacher now is no longer just teaching but also educating, fostering, motivating, and becoming a model for students. Efforts to instill commendable behavior in early childhood can be made through character education if a teacher understands his position. This study sought information about the teacher's position in instilling character education in early childhood at Shafa Marwah Karawang Kindergarten. The method used in this research is qualitative with descriptive analysis. Data collection techniques using passive participatory observation, semi-structured interviews, and documentation. The results of the study show that the teacher's position in the development of early childhood character education at Shafa Marwah Karawang Kindergarten is not only as a learning resource, facilitator, manager, demonstrator, mentor, and evaluator but also has a position as a motivator. Teachers are also motivators because the teachers 1) explain or give direction and guidance on the objectives of each activity carried out, 2) arouse student interest will be encouraged them to learn and get used to it well, 3) use various learning models and strategies, 4) creating a pleasant atmosphere, and 5) giving awards or praise to students after doing commendable things.